A Web-Based Interactive Map to Promote Health-Care Facility Flood Preparedness. (16th June 2022) - Grossman, Elena; Hathaway, Michelle; Khan, Amber; Sambanis, Apostolis; Dorevitch, Samuel
Abstract: Objectives: Little is known about how flood risk of health-care facilities (HCFs) is evaluated by emergency preparedness professionals and HCFs administrators. This study assessed knowledge of emergency preparedness and HCF management professionals regarding locations of floodplains in relation to HCFs. A Web-based interactive map of floodplains and HCF was developed and users of the map were asked to evaluate it. Methods: An online survey was completed by administrators of HCFs and public health emergency preparedness professionals in Illinois, before and after an interactive online map of floodplains and HCFs was provided. Results: Forty Illinois HCFs located in floodplains were identified, including 12 long-term care facilities. Preparedness professionals have limited knowledge of whether local HCFs were in floodplains, and few reported availability of geographic information system (GIS) resources at baseline. Respondents intended to use the interactive map for planning and stakeholder communications. Conclusions: Given that HCFs are located in floodplains, this first assessment of using interactive maps of floodplains and HCFs may promote a shift to reliable data sources of floodplain locations in relation to HCFs. Similar approaches may be useful in other settings.